PENGARUH DETERMINAN FRAUD (FRAUD DIAMOND) TERHADAP KECURANGAN AKADEMIK MAHASISWA AKUNTANSI - Tonasa, Muhamad (IAIN Kendari, 2023)
Universities aim to produce quality professional staff, but students are still found to be results-oriented, leading to the practice of academic cheating or fraud. This phenomenon is global, including in Indonesia. This research aims to obtain empirical evidence about the influence of Fraud Diamond determinants on accounting students' academic fraud. Data from 164 students were analyzed using multiple linear regression. The results show that pressure, opportunity, rationalization, and ability influence fraud. These results can be taken into consideration in minimizing academic fraud and forming the character of accounting students with integrity and honesty.